Muscular mechanics and neuromuscular control - Schmidtbleicher, D. (Swimming Science V, 1988)
In the practice of training, some still believe that strength training merely calls for changes in enzymatic quantity or quality within the muscle, which ultimately results in muscle cross-section increases. Results of ergophysiological and training research on the optimal training stimulus for the greatest possible strength increases appear to come from two distinct sources: • The tension stimulus theory, created by Rasch and Pierson (1964) and Hettinger (1968) stipulates that maximal tension results in the most effective rate of strength increases. • In contrast, the so-called ATP-debt theory from Meerson (1967, 1973) suggests that training with submaximalloads (15 reps in 20 s per set) done repetitively results in the highest strength increases.